The Relationship Between Health Care Transition and Self-care in Chronic Kidney Disease Patients Undergoing Hemodialysis at a Private Hospital - Ayu Rininta Kana; Geovany Latupeirissa; Yuniarti Emmy Monica Pattiwaelapia; Eva Chris Veronica Gultom; Windy Sapta Handayani Zega (NERS Jurnal Keperawatan, 2025)
Chronic Kidney Disease (CKD) is one of the chronic conditions that contributes to global morbidity and mortality, with a continuously increasing prevalence. The management of CKD through hemodialysis requires patients to perform self-care independently and effectively. Self-care is the performance or practice of individual activities to take initiative and shape their behavior in maintaining life, health, and well-being. Health care transition is the process of health changes experienced by a person involving changes in health status, role relationships, and expectations. This indicates the importance of health care transition in improving patients' independence and self-care practices. The aim of this study was to analyze the relationship between health care transition and self-care among patients with Chronic Kidney Disease undergoing hemodialysis at a private hospital. This research employed a quantitative method with a cross-sectional study design. The sampling technique used was purposive sampling, with a total of 126 respondents. The research instruments used were the STARx Questionnaire and the Hemodialysis Patients Self-Care Measurement Scale to assess self-care. The study was conducted from April 14 to 16, 2025. The data analysis techniques included univariate and bivariate analyses using the chi-square test. The results of the univariate analysis showed that the majority of respondents had a good level of health care transition (61.1%) and a good level of self-care (51.6%). The results of the bivariate analysis indicated a significant relationship between health care transition and self-care among CKD patients undergoing hemodialysis at the private hospital. It is expected that health care professionals can optimize support during the health care transition process to enhance patients' independence in performing self-care.